Calcium channel autoimmunity: Cerebellar ataxia and lambert‐eaton syndrome coexisting. Issue 1 (11th January 2018) - Zalewski, Nicholas; Lennon, Vanda A.; Pittock, Sean J.; Mckeon, Andrew
ABSTRACT: Introduction : Neuronal calcium channel antibodies are a biomarker of Lambert‐Eaton syndrome (LES) and cerebellar ataxia. We have encountered several patients with LES and cerebellar ataxia coexisting, and we sought to further define this association. Methods : We reviewed records of patients at our institution with a diagnosis of "Lambert‐Eaton syndrome" and "cerebellar ataxia." Results : Seventeen patients were identified with LES and ataxia. Presenting symptoms were weakness (8), concurrent weakness and ataxia (4), ataxia (4), and other (1). Nine patients had small‐cell lung carcinoma, 3 of whom had survival greater than 100 months. Immunotherapy responses were best among patients without cancer. Nine of 17 (53%) patients were alive at last follow‐up (median survival 62 months; range, 8–240). Discussion : Calcium channel autoimmunity should be considered in patients with coexisting cerebellar ataxia and myasthenic weakness. Affected patients may survive small‐cell carcinoma or have immunotherapy‐responsive neurological symptoms. Muscle Nerve 58 : 29–35, 2018